PENGARUH MUTU PELAYANAN KESEHATAN GIGI DAN MULUT TERHADAP MINAT KUNJUNGAN ULANG PASIEN DI PUSKESMAS CIMAHI SELATAN (Jurnal Kesehatan Siliwangi, 2021)
This study aimed to determine the effect of the quality of tooth and mouth health service on the interest of patient to re-visits Puskesmas Cimahi Selatan. The subjects of this study were 70 people whohad already made a tooth and mouth health visit to Puskesmas Cimahi Selatan. Quantitative approach was used in this research. The meansuring instrument used in this study was the scale of the quality of health care that was arranged based on the dimensions of service quality. Data were analyzed statistically using Chi-Square analysis. The results of the statistical analysis showed that there was a significant influence between the quality of helath services on the interest of patient to re-visits Puskesmas Cimahi Selatan. The indicated that the higher quality of health services , the higher too interest of patient to re-visits Puskesmas Cimahi Selatan.